17‐Year Follow‐Up of Ridge Augmentation in a Patient With Linear Scleroderma: A Novel Case Report. Issue 2 (21st May 2018) - Goldberg, David A.; Pinn, Marvin; Goldberg, Adam S.
Abstract : Introduction: Scleroderma is a chronic autoimmune disease associated with connective tissue changes and fibrosis, which often includes oral manifestations. Involvement of the oral mucosa results in gingival recession, loss of alveolar housing, root resorption, gross mobility, and other deleterious side effects. Therefore, patients may require extensive restorative care, but pathology can often prevent optimal delivery. Case Presentation: The following case presents a patient with localized scleroderma requiring a ridge augmentation for the placement of a fixed partial denture. Following the disease diagnosis and treatment planning, the patient received local subcutaneous injections of 25 mg‐methotrexate to halt disease progression. Given the success of the prophylaxis, the patient underwent three extractions followed by two surgical augmentation procedures, including the placement of xenographic bovine matrix and an overlying connective tissue graft. Healing occurred within normal limits, allowing the successful delivery of a permanent prosthesis. Conclusions: This case presentation is the first to our knowledge to document successful soft tissue ridge augmentation in a patient with localized scleroderma in order to place a fixed bridge; thereby, documenting the feasibility of esthetically restoring patients presenting with said systemic disease. The case uniquely illustrates identification of a rare connective tissue disease that saw successful treatment outcomes due to proper diagnosis, disease management, interprofessional collaboration, and advanced treatment planning.